If the 9th term of an AP is zero, then prove that the 29th term is double of the 19th term.
Answer
Verified
512.7k+ views
Hint- Here, we will be using the formula for finding the nth term of an arithmetic progression in order to write the expressions of 9th term, 29th term and 19th term of an arithmetic progression.
To prove- 29th term is double of 19th term of given AP i.e., ${a_{29}} = 2{a_{19}}$
Let us suppose the first term of an AP as ${a_1}$, common difference as d.
As we know that the nth term of any AP with first term as ${a_1}$ and common difference as d is given by ${a_n} = {a_1} + \left( {n - 1} \right)d{\text{ }} \to {\text{(1)}}$
Given, ${a_9} = 0$
Using equation (1), we have
${a_9} = {a_1} + \left( {9 - 1} \right)d \Rightarrow {a_1} + 8d = 0{\text{ }} \to {\text{(2)}}$
Let us simplify the equation which needs to be proved by putting n=29 in equation (1) for LHS and n=19 in equation (1) for RHS, we can write
$
{a_{29}} = 2{a_{19}} \Rightarrow {a_1} + \left( {29 - 1} \right)d = 2\left[ {{a_1} + \left( {19 - 1} \right)d} \right] \Rightarrow {a_1} + 28d = 2\left( {{a_1} + 18d} \right) \Rightarrow {a_1} + 28d = 2{a_1} + 36d \\
\Rightarrow {a_1} + 8d = 0{\text{ }} \to {\text{(3)}} \\
$
Clearly, the equation which needs to be proved is reduced into equation (3) so in order to prove the required equation ${a_{29}} = 2{a_{19}}$, equation (3) needs to be proved.
Since, equation (2) holds true and equation (3) needs to be proved whereas equations (2) and (3) are the same. Hence, the required equation is proved i.e., ${a_{29}} = 2{a_{19}}$(29th term of AP is double of 19th term of AP).
Note- In these types of problems, we will simplify the equation that needs to be proved with the help of general formulas for an arithmetic progression and then use the already given condition. In this particular problem the given condition is the same equation (obtained after simplification) which needs to be proved.
To prove- 29th term is double of 19th term of given AP i.e., ${a_{29}} = 2{a_{19}}$
Let us suppose the first term of an AP as ${a_1}$, common difference as d.
As we know that the nth term of any AP with first term as ${a_1}$ and common difference as d is given by ${a_n} = {a_1} + \left( {n - 1} \right)d{\text{ }} \to {\text{(1)}}$
Given, ${a_9} = 0$
Using equation (1), we have
${a_9} = {a_1} + \left( {9 - 1} \right)d \Rightarrow {a_1} + 8d = 0{\text{ }} \to {\text{(2)}}$
Let us simplify the equation which needs to be proved by putting n=29 in equation (1) for LHS and n=19 in equation (1) for RHS, we can write
$
{a_{29}} = 2{a_{19}} \Rightarrow {a_1} + \left( {29 - 1} \right)d = 2\left[ {{a_1} + \left( {19 - 1} \right)d} \right] \Rightarrow {a_1} + 28d = 2\left( {{a_1} + 18d} \right) \Rightarrow {a_1} + 28d = 2{a_1} + 36d \\
\Rightarrow {a_1} + 8d = 0{\text{ }} \to {\text{(3)}} \\
$
Clearly, the equation which needs to be proved is reduced into equation (3) so in order to prove the required equation ${a_{29}} = 2{a_{19}}$, equation (3) needs to be proved.
Since, equation (2) holds true and equation (3) needs to be proved whereas equations (2) and (3) are the same. Hence, the required equation is proved i.e., ${a_{29}} = 2{a_{19}}$(29th term of AP is double of 19th term of AP).
Note- In these types of problems, we will simplify the equation that needs to be proved with the help of general formulas for an arithmetic progression and then use the already given condition. In this particular problem the given condition is the same equation (obtained after simplification) which needs to be proved.
Recently Updated Pages
Master Class 11 Accountancy: Engaging Questions & Answers for Success
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Trending doubts
10 examples of friction in our daily life
Difference Between Prokaryotic Cells and Eukaryotic Cells
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
State and prove Bernoullis theorem class 11 physics CBSE
What organs are located on the left side of your body class 11 biology CBSE
Define least count of vernier callipers How do you class 11 physics CBSE